Backpackers or Working Holiday Makers? Working Tourists in Australia - Brennan, Christopher (Qualitative Sociology Review, 2014)
This article looks at a potential divergence of characteristics between backpackers and working holiday makers in Australia. While both are often lumped together within academic study, working holiday makers have a legal right to pursue employment and are entitled to rights and standards of work that come with paid employment, whereas backpackers, as young budget travelers, do not. Drawing on data from autoethnographic fieldwork, qualitative interviews, and empirical analysis of previous studies, this article identifies a conceivable divergence between backpackers and working holiday makers in Australia: the activity of paid employment. The investigation highlights empirical factors and circumstances that contribute to a separation as compared to previous discussions and studies. The paper concludes by suggesting that more emphasis should be given to working holiday makers as a distinct group of working tourists who, in fact, have rights as workers, disjoining them from the label “backpacker,” which is more commonly understood as a form of young budget tourist.